26-5x=-7-3r

Simple and best practice solution for 26-5x=-7-3r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26-5x=-7-3r equation:


Simplifying
26 + -5x = -7 + -3r

Solving
26 + -5x = -7 + -3r

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + -5x = -7 + -26 + -3r

Combine like terms: 26 + -26 = 0
0 + -5x = -7 + -26 + -3r
-5x = -7 + -26 + -3r

Combine like terms: -7 + -26 = -33
-5x = -33 + -3r

Divide each side by '-5'.
x = 6.6 + 0.6r

Simplifying
x = 6.6 + 0.6r

See similar equations:

| 4(u-4)-6u=4 | | 20-4(2w+1)=6w-4(6+w) | | (-8y-5)(7y)y=-3 | | 8c-3d=6 | | 1d+8=2d-17 | | 0.7m+0.3m=2m-4 | | p=m+k+n | | -6(x-3)-4(6-6x)=12 | | -6-3(6+4x)=-24-2x | | 91=-7(2n-7) | | -5*(1/9+x)=0 | | 114=(x+2)15-3x | | -(4y+3z-4)= | | x+1(2)+x(2)=14 | | 2x+8=8+2x | | 18=c+5/2 | | (x+2)(x-1)(x+1)=0 | | -5a+2a=12-15 | | 15-2(2w+1)=7w-2(7+w) | | -187=2-7(4x+7) | | 9l=3m | | 5(-5-3p)=-8p+3 | | 7t-(t-4)=25 | | (4a-4)(4a-1)=0 | | 0.7n+4.7=5.4n | | 5a+2a=12-15 | | -7(-3m-8)=98 | | 10-3(4x-2)=5x | | 4x-9=2x+1 | | 10x-7=5(x+1) | | 4x-29.2=7.5x-6.8 | | 3g-21=20+2g |

Equations solver categories